2019
DOI: 10.1080/24750573.2019.1589176
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammatory response in patients with psoriasis; is there any relationship with psychiatric comorbidity and cognitive functions?

Abstract: Objectives: Psoriasis is a chronic, inflammatory skin disease which has been linked to psychopathology. Oxidative stress and inflammation are associated with atherogenesis and neuronal stress thus, cognitive functions might be impaired in psoriasis patients. We aimed to compare psychiatric comorbidity, neurocognitive functions, oxidative stress and inflammatory cytokine levels in psoriasis patients with healthy controls, besides to evaluate the effect of oxidative stress and inflammation on comorbidity and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…The result of the comparison of [TOS] levels terms of gender(Table 2) show that in bothsera and saliva samples, a highly significant increase is obvious (P˂ 0.001) between the patients subgroup compared compared with healthy control [21] . As well as with Sezeret al [22] andSkoieet al [23] who studiedmalondialdehyde (anend product marker of lipid peroxidation)sera samples.Ourfinding are consistent with those reported by other authors such as Tanhapouret alwho recorded an increased level of tissue malondialdehyde and oxidized low density lipoprotein [LDL] which are considered as markers of oxidative stress [24] .…”
Section: Resultsmentioning
confidence: 99%
“…The result of the comparison of [TOS] levels terms of gender(Table 2) show that in bothsera and saliva samples, a highly significant increase is obvious (P˂ 0.001) between the patients subgroup compared compared with healthy control [21] . As well as with Sezeret al [22] andSkoieet al [23] who studiedmalondialdehyde (anend product marker of lipid peroxidation)sera samples.Ourfinding are consistent with those reported by other authors such as Tanhapouret alwho recorded an increased level of tissue malondialdehyde and oxidized low density lipoprotein [LDL] which are considered as markers of oxidative stress [24] .…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Gisondi et al, 23 Colgecen et al 20 and Marek-J ozefowicz et al 21 mainly included patients with higher disease severity (mean PASI ≥ 15), resulting in the potential for selection bias. However, Deveci et al 32 also found lower cognitive test scores in mild psoriasis cases (most with PASI ≤ 5).…”
Section: Critical Appraisal Of the Evidencementioning
confidence: 94%
“…Deveci et al evaluated 37 psoriasis cases (most cases PASI ≤ 5) and 37 controls in a cross-sectional study. 32 Cognitive test score results were lower in patients with psoriasis compared with controls. Additionally, the blood levels of proinflammatory cytokines, a and IL-6, were significantly higher in patients with psoriasis.…”
Section: Cognitive Impairment In Patients With Psoriasismentioning
confidence: 94%
See 1 more Smart Citation
“…Psoriasis patients are more susceptible to mental health diseases than patients with other dermatological conditions [3]. It is recognized that the risk of depression, anxiety, and suicidality is higher in patients with psoriasis [4]. The impact of psoriasis on patients' lives can be assessed by different instruments, namely, the Psoriasis Disability Index (PDI) [5].…”
Section: Introductionmentioning
confidence: 99%